Pain mechanism and management strategy of rheumatoid arthritis - Wang, Dijun; Li, Ting; Wang, Weiqi; Ruan, Yonglan; Cai, Jiali; Yan, Xiaojing (Frontiers in Pain Research, 2025)
Rheumatoid arthritis (RA) pain is one of the most common forms of chronic pain in clinic. A large number of RA-related literature has been reported. At present, although some analgesic measures are used in clinic, pain management after drug treatment remains suboptimal in real-world settings, and clinically meaningful pain after treatment is still reported. RA pain is a complex pathological process that involves inflammatory response, neuroimmune interaction, peripheral and central nerve sensitization, autoantibodies, structural damage, and other dimensions. Although inflammatory reaction is the most common cause of RA-induced pain, neuroimmune interaction is the key and core of RA pain, and autoantibodies are one of the significant characteristics of RA, which can directly or indirectly lead to pain. In addition, joint structural damage is the final pathological stage and a serious consequence in the late stage of RA. This article aims to summarize the mechanisms of RA pain, which is helpful to further clarify the diagnosis and provide targeted treatment.